MENINGKATKAN KEMAMPUAN EKSPLORASI GERAK TARI KREASI BAGI SISWA KELAS VIII E SMP NEGERI 44 JAKARTA TIMUR MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIVEMENT DIVISION (STAD) - Mustakim, Amirul; Kusumawardani, Dwi; Mutiara Sari, Kartika (Jurnal Pendidikan Tari, 2025)
This study aims to analyze and describe the implementation of the Student Team Achievement Division (STAD) cooperative learning model in enhancing the movement exploration skills of creative dance among eighth-grade students at SMP Negeri 44 Jakarta Timur. The study was motivated by the low level of students' movement exploration skills in creating creative dance. The research employed classroom action research using Kurt Lewin’s cyclical model, consisting of planning, action, observation, and reflection. The subjects were 36 students from class VIII E. Data were collected through observations, interviews, documentation, and dance performance tests. The findings indicate that the implementation of the STAD model significantly improved students’ movement exploration, with post-test scores increasing by 77% based on the N-Gain test, classified as high and effective. The STAD model encourages students to engage actively in groups, enhances creativity, and deepens their understanding of dance elements. In conclusion, the STAD cooperative learning model is effective in improving creative dance movement exploration skills while supporting collaborative learning and creativity in dance education.